2012
DOI: 10.1002/jps.23265
|View full text |Cite
|
Sign up to set email alerts
|

Vorinostat with sustained exposure and high solubility in poly(ethylene glycol)‐b‐poly(dl‐lactic acid) micelle nanocarriers: Characterization and effects on pharmacokinetics in rat serum and urine

Abstract: The histone deacetylase inhibitor suberoylanilide hydroxamic acid, known as vorinostat, is a promising anti-cancer drug with a unique mode of action; however, it is plagued by low water solubility, low permeability, and suboptimal pharmacokinetics. In this study, poly(ethylene glycol)-b-poly(DL-lactic acid) (PEG-b-PLA) micelles of vorinostat were developed. Vorinostat’s pharmacokinetics in rats were investigated after intravenous (i.v.) (10 mg/kg) and oral (50 mg/kg) micellar administrations and compared to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…However, Taxotere ® caused hypersensitivity reactions and fluid retention in beagle dogs, whereas Nonoxel-PM ™ has no such effects in beagle dogs. Interestingly, PEG- b -PLA micelles did significantly modify the pharmacokinetic parameters of vorinostat, an HDAC inhibitor, compared to a conventional formulation of PEG400 in rats [29]: Mean residence time increased by two orders of magnitude, dramatically increasing exposure of vorinostat. It is noted that the molecular weight of PEG and PLA was relatively high, ca.…”
Section: Peg-b-pla Micellesmentioning
confidence: 99%
“…However, Taxotere ® caused hypersensitivity reactions and fluid retention in beagle dogs, whereas Nonoxel-PM ™ has no such effects in beagle dogs. Interestingly, PEG- b -PLA micelles did significantly modify the pharmacokinetic parameters of vorinostat, an HDAC inhibitor, compared to a conventional formulation of PEG400 in rats [29]: Mean residence time increased by two orders of magnitude, dramatically increasing exposure of vorinostat. It is noted that the molecular weight of PEG and PLA was relatively high, ca.…”
Section: Peg-b-pla Micellesmentioning
confidence: 99%
“…Recently, much effort has been devoted to designing delivery carriers for vorinostat (HDACi), for example using copolymer micelles of poly (ethylene oxide) (PEO)-polylactic acid (PLA). These carriers have improved vorinostat solubility up to 40-fold, improved the pharmacokinetics, extended circulation half-life, and decreased clearance [140,141]. Furthermore, the therapeutic index of vorinostat was improved by developing acid sensitive delivery system out of a pro-drug of vorinostat [142].…”
Section: Particulate Delivery Of Epigenetic Modulatorsmentioning
confidence: 98%
“…administration remains a challenge due to their limited aqueous solubility and poor PK in vivo (10, 11). To address these challenges, a recent study has reported on the use of poly(ethylene glycol)-b-poly(DL-lactic acid) (PEG-b-PLA) micelles to encapsulate SAHA to improve both solubility and PK of the drug (12). In another example, LAQ was successfully entrapped into targeted immunoliposomes via formation of a complex between LAQ and a polymer, polyanionic polyol sucrose octasulfate (SOS), resulting in prolonged PK and improved antitumor properties (13).…”
Section: Introductionmentioning
confidence: 99%